Micro-mechanism analysis of enhanced oil recovery for positive-negative drive. (15th January 2020) - Zhang, Jingchen; Wang, Mingxing; Dong, Jingfeng; Shi, Shanzhi; Wang, Chenchen; Yang, Yan; Nicholas Izuchukwu, Osuji
Abstract: The positive and negative displacement field experiments have achieved good yield increase. The existing researches mainly focus on the microscopic mechanism site and reservoir non-homogeneity. At present, there is no relevant research on the change of crude oil state, quantitative statistical analysis and stimulation mechanism caused by positive and negative displacement in core scale. In this research, the core is subjected to positive and negative displacement and then imaged by quasi-real-time CT scan. The pore network model software is used to quantitatively analyze the oil-water distribution information at different moments in the core. Furthermore, the characteristics of reservoir pores, oil and water occurrence characteristics, positive and negative displacement increased mechanisms and seepage characteristics are clarified. From the study, it is observed that during the whole water flooding process, the volume fraction of the cluster flow gradually decreases. The cluster flow is continuously displaced or broken into other discontinuous phase flow states; multi-porous, columnar, droplet, membranous as a discontinuous phase. The volume percentage increases with the progress of the displacement process, and the increase of multi-porous flow is most obvious during the reverse drive process. The significant reduction of cluster flow during the anti-drive process is the main mechanism for anti-drive production.